La tarification douanière dans un optimum de compromis - Bronsard, Camille; Kabuya, F. (L'Actualité économique, 1976)
AbstractThe purpose of this paper is to integrate into a general model of an open economy the study of optimal wedges on domestic and foreign transactions.While it has been customary in the literature to link the analysis of domestic taxes to the provision of public goods, the model presented here views the imposition of taxes and tariffs in the general context of internal and external monopolies. As such, the paper begins with the idea of a compromised optimality. This means essentially that a modern society, while maximizing the welfare of its members, is constrained by other internal objectives such as the fact that the State shares its monopoly power with several other economic entities (for instance employers' federations, trade-unions). Thus, the mere fact of levying taxes gives a State some monopoly power which, in a sense, is similar to that of a Cournot-type monopolist who "imposes" private taxes.On the other hand, given the possibility that a country with some monopoly power in international trade could improve its situation by imposing tariffs, the analysis lends itself to the study of tariffs and taxes in the broad context of optimal wedges. To allow for this characterization, the paper incorporates into the model of normalization. As a by-product of this, a) it establishes, in terms of generalized inverses of the Slutsky matrix, a link between domestic marginal relative revenues and foreign ones; b) it defines two concepts of optimal tariffs evaluated from f.o.b. prices and c.i.f. prices; c) it suggests some further extensions such as the analysis of transactions costs, the incorporation of market retaliations and cultural characteristics of goods.